Exploring User Attitudes and Trust Toward ChatGPT as a Social Actor: A UTAUT-Based Analysis - Hwan-Ho Noh; Hye Bin Rim; Byung-Kwan Lee (SAGE Open)
Recent advancements in artificial intelligence (AI) have transformed consumer services with technologies such as AlphaGo surpassing human capabilities. OpenAI’s ChatGPT positioned AI as a social actor. This study examines ChatGPT’s natural language prowess using AI from the perspective of social actors. We investigated user attitudes through the Unified Theory of Acceptance and Use of Technology (UTAUT) while employing the stereotype content model to assess ChatGPT’s portrayal as a social actor. Trust is an important factor when considering ChatGPT as a social actor. Our model validation revealed that “performance expectancy and facilitating conditions” significantly impacted ChatGPT evaluation, “social influence” affected usage intentions, and “effort expectancy” had no significant effect. In the stereotype content model, warmth and competence significantly influenced trust and performance expectations. Trust in the ChatGPT emerged as the main predictor of the evaluation. The study concludes with a discussion of the implications, accounting for differences in user experience (UX).